PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS HOTS BERBANTUAN MEDIA LEGO TERHADAP KEMAMPUAN METAKOGNISI MATEMATIS MATERI PECAHAN PADA PESERTA DIDIK KELAS III SD SEKECAMATAN SUKARAMI PALEMBANG - Wahyunia Gustini; Fajri Ismail, Puryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the HOTS-based Problem Based Learning model assisted by Lego media on mathematical metacognition abilities in fraction material in grade III students of Public Elementary Schools in Sukarami District. Research samples were taken using the Cluster Random Sampling technique. The two selected schools were SD Negeri 127 Palembang, namely class IIIA as the control class and SD Negeri 128 Palembang, namely classes IIIA and IIIB as the experimental. The type of research used is True Experimental with a quantitative approach. This research uses a Pretest Posttest Control Group Design form.The research hypothesis was tested using a one-way ANOVA test with the F-test statistical test and continued with the t-dunnet further test. The results of the study concluded that: (1) there is a significant influence of mathematical metacognitive ability between students who receive learning with the HOTS-based Problem Based Learning learning model assisted by Lego media, HOTS-based Problem Based Learning without Lego media and conventional; (2) there is a difference in the average mathematical metacognitive ability of the HOTS-based Problem Based Learning group assisted by Lego media and HOTS- based Problem Based Learning without Lego media; (3) The average mathematical metacognitive ability of the HOTS-based Problem Based Learning group assisted by Lego media is higher than the group given the conventional method; (4) The average mathematical metacognitive ability of the HOTS-based Problem Based Learning group without Lego media is lower or the same as the mathematical metacognitive ability of the group with the conventional method.